The Effect of Self Help Group on Knowledge and Attitude in Decision Making Among Household Head of Patients with Depression in Yogyakarta - Endang Tri Sulistyowati; Bhisma Murti; Yulia Lanti Retno Dewi (Masters Program in Public Health, Sebelas Maret University, 2016)
Background: Treatment of patients with mental health problem at home and hospital has been so variable and unsatisfactory. An often assumed causal factor of this problem is lack of knowledge among household heads of patients with mental health problem. This study aimed to determine the effect of self help group on knowledge and attitude in decision making among household heads of patients with depression in Yogyakarta.Subjects and Method: This was an analytic experimental study with RCT (Randomized Control Trial). This study was conducted at Jetis, Sleman, Yogyakarta. Study subjects included household heads and 60 patients with depression. The dependent variables were knowldege and attitude in decision making. The independent variable was self health group. The data were collected by use of a set of questionnaire. The data were analyzed by logistic regression.Results: There was positive relationship between engaged in self help group and knowledge (OR= 1.46, 95% CI= 1.33-14.02, p= 0.015) among household heads of patients with depression. There was positive relationship between being engaged in self help group and attitude, but it was statistically non-significant (OR= 1.46, 95% CI= 0.74-25.41, p= 0.105).Conclusion: Self help group has positive significant effect on household head’s knowledge, as well as attitude in decision making among household heads.Keywords: self help group, knowledge, attitudeCorrespondence: Endang Tri Sulistyowati. Health Academy of Karya Husada, Yogyakarta. Email: endangts80@gmail.com.Journal of Health Promotion and Behaviour (2016), 1(4): 223-227https://doi.org/10.26911/thejhpb.2016.01.04.01